Prevalence of autoantibodies to the 65- and 67-kD isoforms of glutamate decarboxylase in insulin-dependent diabetes mellitus. - Seissler, J (1993)
We investigated the presence of autoantibodies to baculovirus-expressed human recombinant 65- and 67-kD isoforms of glutamate decarboxylase (GAD65 and GAD67) in insulin-dependent diabetes mellitus (IDDM). In the immunoprecipitation test using [35S]methionine-labeled GADs antibodies to GAD65 were detected in 13/15 (87%) islet cell antibody (ICA)-positive and in 1/35 (2.9%) ICA-negative first-degree relatives of patients with IDDM, in 6/11 (54.5%) ICA-positive nondiabetic schoolchildren, and in 35/50 (70%) patients with newly diagnosed IDDM. GAD67 antibodies were positive only in five (33%) of the ICA-positive relatives (P < 0.05) and in nine (18%) IDDM patients at onset (P < 0.00001). After onset of IDDM antibodies to GAD65 and GAD67 declined but were still positive in 25 and 9.4% of subjects with long-standing IDDM (> 10 yr). In all study groups antibodies to GAD67 were only detected in GAD65 antibody-positive sera. An immunotrapping enzyme activity assay for GAD65 antibodies was positive in 64/75 (85.3%) of sera that were GAD antibody positive in the immunoprecipitation test (r = 0.870, P < 0.0001). In two (2.7%) sera GAD65 antibodies that block GAD enzyme activity were found. Our data suggest that antibodies to GAD65 but not to GAD67 represent sensitive markers for preclinical and overt IDDM. The immunotrapping assay here described represents a valuable technique for specific and sensitive screening for GAD antibodies.